A Companion to the City of Rome - Claridge, Amanda (Blackwell Companions to the Ancient World Ser, 2018)
Intro -- Title Page -- Copyright Page -- Contents -- Preface -- Abbreviations -- List of Illustrations -- List of Tables -- List of Maps -- Part I Introductory -- Chapter One -- i Archaeological Sources -- Guide to Further Reading -- Digital Resources -- References -- ii Written Sources -- Guide to Further Reading -- References -- iii The Marble Plans -- Guide to Further Reading -- References -- iv The Epigraphic Record -- Guide to Further Reading -- References -- v Coins -- Guide to Further Reading -- References -- Chapter Two Historical Overview: From City-state to Christian Center -- Beginnings -- The Consequences of Growth -- Towards Monarchy -- Imperial Rome -- Decline and Fall? -- Guide to Further Reading -- References -- Part II The Urban Landscape -- Chapter Three A City of Stories -- The Trader: Eumakhos of Milētos, c. 525 bce -- The Lawgiver: Hermodoros of Ephesos, c. 450 bce -- The Ambassador: Kineas of Thessalia, 280 bce -- The Rhetorician: Diophanes of Mitylēnē, 133 bce -- The Astrologer: Thrasyllos of Alexandreia, 2 ce -- Suggestions for Further Reading -- References -- Chapter Four Defining the City: The Boundaries of Rome -- Introduction -- Defending and Defining: The City Walls -- Religion and politics: The pomerium -- A Practical Perspective: Law, Taxation and Administration -- Man and nature: The Tiber -- The Power of the Past: Boundary Traditions -- Conclusion -- Guide to Further Reading -- References -- Chapter Five The Development of the City: An Archaeological Perspective -- i) From its Origins to the Second Century bce -- ii) From 100 bce to 600 ce -- References -- Part III The People -- Chapter Six The Population -- Counting the inhabitants of Rome: The methodological problem -- The Dynamics of the Population: Immigration and Natural Reproduction -- Causes of decline -- Guide to Further Reading -- References.